NORMAL FUNCTIONS AS A NEW WAY OF DEFINING COMPUTABLE FUNCTIONS - Dubiel, Leszek (Computer Science, 2013)
Report sets new method of defining computable functions. This is formalization of traditional function descriptions, so it allows to define functions in very intuitive way. Discovery of Ackermann function proved that not all functions that can be easily computed can be so easily described with Hilbert’s system of recursive functions. Normal functions lack this disadvantage.